Emotional bodies : the historical performativity of emotions - Martín-Moruno, Dolores; Pichel, Beatriz (History of emotions., 2019)
"What do emotions actually do? Recent work in the history of emotions and its intersections with cultural studies and new materialism has produced groundbreaking revelations around this fundamental question. In Emotional Bodies, contributors pick up these threads of inquiry to propose a much-needed theoretical framework for further studying the materiality of emotions, with an emphasis on emotions' performative nature. Drawing on diverse sources and wide-ranging theoretical approaches, they illuminate how various persons and groups-patients, criminals, medieval religious communities, revolutionary crowds, and humanitarian agencies-perform emotional practices. A section devoted to medical history examines individual bodies while a section of social and political histories studies the emergence of collective bodies. Contributors: Jon Arrizabalaga, Rob Boddice, Leticia Fernández-Fontecha, Emma Hutchison, Dolores Martín-Moruno, Piroska Nagy, Beatriz Pichel, María Rosón, Pilar León-Sanz, Bertrand Taithe, and Gian Marco Vidor"--